A STUDY ON THE FIFTH SEMESTER STUDENTS’ READING STRATEGIES AT THE ENGLISH STUDY PROGRAM OF RIAU UNIVERSITY - Dwitiya Febriyanti; Novitri '; Syofia Delfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The objective of this descriptive research was to find out about students’ reading strategies in their reading activities, inside and outside the classrom. The sample of this research was the fifth semester students of English Department of Riau University. There were 65 students participated as the sample of this research. The data were quantitative and the instrument of the research was a questionnaire which consists of 28 questions regarding the reading strategies they use inside and outside the class. The data were analyzed by calculating the score of the students in answering the questionnaire and classifying them to a certain category using Sugiono formula (2012). The results were that out of 65 students, the students’ response is strongly agree with the reading strategies such as: Identifying the purpose in reading (81,23%), using different silent reading techniques for relatively rapid reading (80,61%), analyzing vocabulary (80%), and guessing when we are not certain(80,30%). After that, the students’ response is agree such as : Using graphemic rules and patterns to aid in bottom-up reading (76%), skimming the text for main ideas (73,23%), scanning the text for specific information (73,53%), using semantic mapping or clustering (70,76%), distinguishing between literal and implied meanings (75,07%), and capitalizing on discourse markers to process relationships (74,15). This research recommended that the students to find out the suitable reading strategies for doing their reading activities. Further research can focus on studying each subtopic in details.Keywords: reading strategies, reading activities